Topical combined application of dexamethasone, vitamin C, and β-sodium glycerophosphate for healing the extraction socket in rabbits. Issue 10 (October 2015) - Chen, J.; He, Y.; Shan, C.; Pan, Q.; Li, M.; Xia, D.
Abstract An osteogenic inducer (OI) consisting of dexamethasone, vitamin C, and β-sodium glycerophosphate has the capacity to induce bone formation in vitro. The aim of this study was to assess the efficacy of the application of this OI on extraction socket healing. The bilateral first mandibular premolars were extracted from 75 New Zealand rabbits. Gelatin sponges carrying OI were implanted into the sockets. Sockets undergoing implantation of gelatin sponges alone were also evaluated, as well as non-implantation sockets. Specimens from each group were evaluated radiographically, histologically, and histomorphometrically using haematoxylin–eosin staining. Results showed earlier new bone formation and higher bone quality and quantity in the OI group compared to the other groups, and the differences were significant at 2, 4, 8, and 12 weeks postoperative. The OI significantly reduced the absorption of alveolar bone in terms of height; however, changes in the width were not significantly different between the three groups (P > 0.05). The OI was shown to have a positive effect on healing of the tooth extraction sockets, was inexpensive, and was convenient to use during the operational procedure; therefore this could represent a promising implant material for human clinical application.